Exploration and selection of native macrofungi with heavy metal tolerance for bioremediation in Jakarta Bay, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Noverita, Ratnaningtyas INI, Hernayanti, Ekowati N, Lestari S. 2025. Exploration and selection of native macrofungi with heavy metal tolerance for bioremediation in Jakarta Bay, Indonesia. Biodiversitas 26: 1940-1955. The increasing pollution of heavy metals Pb and Cd in Jakarta Bay poses a potential threat to marine biota, endangering human health. Macrofungi, known for their ability to mitigate heavy metal pollution through biosorption, are the focus of this research. The study aimed to collect macrofungi from West Sumatra Forest, selectively identifying species that are adaptive to salinity and heavy metals Pb and Cd, possessing a high Heavy Metal Tolerance Index (IT). Field exploration was conducted using a roaming method across 5 forest areas in West Sumatra, followed by laboratory cultivation and systematic screening. A descriptive analysis of fungal exploration data based on morphological characteristics was conducted. Selection results, measured by colony surface area on various treatment media (PDA, PDA with seawater, PDA with Pb/Cd, and PDA with seawater and Pb/Cd), and IT data were analyzed descriptively using GraphPad version 8 heatmaps. This study found that 94 macrofungal species were successfully isolated from 5 forest areas in West Sumatra, comprising 92 species from Basidiomycota and 2 species from Ascomycota. All isolated species demonstrated the capability to grow on various selection media, with varying degrees of adaptation. Nine species, including Coprinus comatus, Favolus tenuiculus, Ganoderma applanatum, Lepiota ristata, Marasmius sp. 21, Polyporus badius, Polyporus elegans, Polyporus sp., and Trametes cubensis, exhibited optimal growth on all media. Statistical analysis with ANOVA (Analysis of Variance) revealed that four species C. comatus, P. elegans, Marasmius sp. 21, and F. tenuiculus, consistently showed superior performance across all test conditions. The Heavy Metal Tolerance Index for Pb and Cd across all species was excellent, with 74% classified as very high, 22% as high, and 4% as moderate. These findings suggest significant potential for utilizing these fungal species in marine bioremediation applications.
Keywords: Biosorption, exploration, macrofungi, selection, Tolerance Index